Can Psychological Contracts Decrease Opportunistic Behaviors? - Zhang, Leinan; Zeng, Qingyan; Yang, Liu; Han, Yan; Xu, Yixin (Frontiers in Psychology, 2022)
Behavioral psychology is increasingly important in relationship marketing. As key factors of emotional interactions between buyer and seller, psychological contracts and opportunistic behaviors play a critical role in interorganizational relationships which are based on personal relationships of boundary spanners and top management. Most of the existing research mainly focus on positive performance of cooperation but ignoring the dark side of relationships. This study introduces the psychological contract into the exploration of why formal contracts cannot completely avoid opportunistic behaviors. It mainly investigates whether psychological contracts in relationships can reduce the occurrence of opportunistic behaviors. The results show that psychological contract has a significant positive effect on the relationship quality, and negatively affect opportunistic behavior through trust and commitment. The positive relationship between psychological contracts and relationship quality is moderated by dependence. This study enriches and expands the domestic and foreign research on psychological contracts and opportunistic behaviors in relationship marketing.